Kontribusi Pancasila di Kancah Internasional: Eksplorasi Nilai-Nilai Perdamaian Qur’ani dari Bingkai Keindonesiaan - Rahmah, Lifa Ainur (JURNAL AT-TURAS, 2020)
Issues regarding peace issues and conflicts are always heavily discussed. Not surprisingly, there are many events that are oriented to re-establishing peace and harmony. Indonesia with the largest Muslim population, remains known as a peaceful residence and can manage diversity. The proof, it is not Islam that is used as an ideology, but Pancasila. But this ideology is rich in noble values that strengthen the solidarity of Indonesian people. In this article, the author tries to explore the values of peace and harmony that read the verses of the Qur'an from the life of the Indonesian people. The trident ethos in Pancasila is the focus of the review of this article. Besides Pancasila is Indonesia's ideology, a country that has an important role in peace in the international world, another reason for the author is that Pancasila is inseparable from the spirit of Islam, a religion of moderate character. Keywords: Peace, Pancasila, Interpretation, and Qur’an.